Public Administration Study Program, Department of Administration Science, Faculty of Social and Political Sciences, University of Riau, Pekanbaru, Indonesia - Rani Nehemia K; Adianto (ADISAM Publisher, 2022)
The field of housing and slums is one of the fields related to programs and activities to preserve the environment of karimun district. This policy is supported by the regional regulation of Karimun Regency Number 1 of 2018 concerning prevention and Improvement of the Quality of Slum Housing and Slums. The purpose of this study was to determine and identify the factors inhibiting the implementation of preventive policies and improve the quality of slum housing and slums in Sei Lakam Timur village in 2020. The research was conducted using qualitative methods with a case study approach. With data collection techniques are carried out through interviews and documentation. The results of the study found that the implementation carried out by the Housing and Settlement Area Office had gone quite well, but in the process there were still obstacles that caused the program to not be optimally running. Based on these findings, implementors should improve coordination with relevant agencies in empowering the community. This effort is made to optimize each program carried out to be in accordance with expectations.